Republic of Armenia : Reducing Poverty and Improving Shared Prosperity through Better Jobs, Skills, and Education - World Bank (Washington, DC, 2017)
This education report is a compliment to the 2017 World Bank led Armenia Systematic Country Diagnostic (SCD), which focuses on how to improve shared prosperity and reduce poverty in Armenia. This report collates information from recent education studies addressing issues with skills development and gender and spatial differences in educational level and quality. Concurrently, this study will try to link key macroeconomic and demographic issues to issues related to the education sector. Thus, this study will provide an overview of the external and internal issues related to improving education and be central with regards to the direction set out in the SCD linking these to poverty and shared prosperity. This study is organized into four main sections intended to provide a comprehensive analysis of Armenia’s education landscape. It will begin with an overview of Armenia’s current social and economic context and the factors that have contributed to it. Next, it will dive deeper into the relationship between education and the economy and unique spatial aspects associated with income and education inequalities. It will then assess the key challenges within the education system that are contributing to Armenia’s current state of affairs. Finally, the study will present policy recommendations based on the information analyzed. In doing so, the aim will be to equip the Republic of Armenia with a strong set of evidence-based education policies and strategies that will promote broad-based prosperity and poverty reduction and move Armenia forward in the next stage of development.